Determining if low dose hyper-radiosensitivity (HRS) can be exploited to provide a therapeutic advantage: A cell line study in four glioblastoma multiforme (GBM) cell lines. (December 2013) - Schoenherr, Diane; Krueger, Sarah A.; Martin, Lynn; Marignol, Laure; Wilson, George D.; Marples, Brian
Abstract Purpose: To determine if ultra-fractionation using repeated pulses of radiation (10 × 0.2 Gray [Gy]) would be more cytotoxic than continuously-delivered radiation to the same total dose (2 Gy) in four glioma cell lines. Materials and methods: Human T98G, U373, U87MG and U138MG cells were conventionally X-irradiated with 0.1–8 Gy and clonogenic survival assessed. Next, cells were treated with either a single dose of 2 Gy or 10 pulses of 0.2 Gy using a 3-min inter-pulse interval and DNA (Deoxyribonucleic acid) repair (pHistone H2A.X), G2-phase cell cycle checkpoint arrest (pHistone H3) and apoptosis (caspase-3) compared between the two regimens. A dose of 0.2 Gy was selected as this reflects the hyper- radiosensitivity (HRS)/increased radioresistance (IRR) transition point of the low-dose cell survival curve. Results: T98G, U87MG and U138MG exhibited distinct HRS responses and survival curves were well-described by the Induced Repair model. Despite the prolonged delivery time, ultra-fractionation (10 × 0.2 Gy) was equally effective as a single continuously-delivered 2 Gy dose. However, ultra-fractionation was more effective when given for five consecutive days to a total dose of 10 Gy. The increased effectiveness of ultra-fractionation could not be attributed directly to differences in DNA damage, repair processes or radiation-induced apoptosis. Conclusions: Ultra-fractionation (10 × 0.2 Gy) is an effective modality for killing glioma cell lines compared with standard 2 Gy dosing when multiple days of treatment are given.